PENENTUAN DENSITAS SPESIES PLASMA HIDROGEN PADA KESETIMBANGAN TERMODINAMIK TEKANAN ATMOSFIR MENGGUNAKAN MATLAB - Reeky Fardinata; Saktioto Saktioto (Universitas Riau, 2019)
Thermal equilibrium hydrogen plasma at atmospheric pressure were simulated using the software matrix laboratory (MATLAB). Runge Kutta method numerical method as a settlement of differensial model equations of chemical kibetik with the arrhenius equation approach and continuity equations so that the equilibrium density values for each species were obtained. Equilibrium hydrogen plasma at atmospheric pressure and density rate review every reaction involved. Parameter of ionizing and disasosiasi as a reference equilibrium plasma. Equilibrium plasma is found in time interval 10-6 – 10-3 s thermal hydrogen plasmas with temperatures of 1 eV. The density of hydrogen plasma thermal equilibrium overall are in the interval of 1014 m-3 - 1020 m-3 . The reaction rate of each species varies based on the type of collision and rate of change of species.